It takes a village - Styf, Anna (My University, 2022)
An ecovillage plans to be built in the northern outskirts of Gothenburg municipality. The ecovillage association - Grönbo - requests a master plan to be formed and designed within the area. This thesis investigates how the village can be built in order to foster social cohesion, cooperation and inclusion. In order to do so, aspects of social resilience is researched. Case studies of different housing projects such as co-housing and ecovillages are investigated to better understand and highlight some of the aspects that fosters social cohesion and use of the common arenas. Additionally, knowledge from city planning and the municipality’s own visions of a socially sustainable Gothenburg is enhanced. The result of the theory and the adaptation to the site’s context and size of the village, the village plan suggests to include a diverse supply of housing typologies where also smaller house sizes are included. The diversity is put together within courtyards with high amounts of shared outdoor space and indoor space that facilitates sharing and cooperation within the area. The spectrums of spaces are a unique variety within this farmland context, and aims at pushing boundaries of our conceptions of private and public. It hence invites the ecovillage association to create groups and undergroups with different responsibilities within the cooperative structure. Apart from the diversity and spectrums of spaces; a third aspect is highlighted, that is to direct people to the common arenas. The shared spaces can be considered common arenas, but the community facilities in the heart of the farming landscape and intersection of existing and new roads are crucial for the social cohesion. It aims at bringing people of the neighboring housing areas together. It provides functions that are needed on a daily and weekly basis, and functions that can be of extra value for the community, individuals and other local networks. Creating visibility and foundations for spontaneous meetings are made through mixed functions within the community house. A co-managed cooperative food store becomes an important factor for facilitating the life within the village where the distance to other food stores risks at creating a daily dependency on cars. The food store could offer core amenities for the inhabitants. The farmland also have a prominent position within the village. Interests of gardening and farming can bring people together in allotment areas, but also highlighting the potential of Grönbo to become one of the areas within Gothenburg that could contribute to an increased self-reliance within the region. Lastly, a village road - Grönbo bygata - cuts through the landscape and connects the village with a bigger villa area that further takes you onto a commuting node from where you easily reach both Kungälv and Bohus towns and Gothenburg city centre. This forms an increased connectivity to other housing and infrastructure through making it easier to bike and walk. This gravel road invites a sustainable way of travel, and additionally works as a community backbone that links the different courtyards and community space together.
Keywords: Community, housing, village, rural planning, social resilience